Optical and structure characteristics of vacuum-deposited layers - Drobyshev, A.S. (Физика низких температур, 1996)
We report results of a complex study of growth rates, refractive indexes, and structure of real cryocrystals of nitrous oxide as well as light and heavy water. The corresponding experimental setup and the relevant experimental procedures are described. We demonstrate possibilities of the available experiment-and-computing complex for the purposes of studying growth kinetics, thermal properties, and structure-morphologic characteristics of real cryocrystal quench-condensed deposits. A structure transformation from the low-temperature highly amorphized state to the Pa3 structure has been observed at a temperature near 40 К in nitrogen monoxide. The spectrum of spontaneous luminescence bursts of freshly prepared N₂O samples has been measured. It consists of two main bands in the red and blue domains of the visible spectral range. Existence of three structural modifications of vacuum condensed water deposits has been confirmed and their temperature boundaries of existence revised. Our results on heavy water cryocondensates allowed us to infer ultrapolymorphism in this solid.